Dietary Cottonseed Protein Substituting Fish Meal Induces Hepatic Ferroptosis Through SIRT1-YAP-TRFC Axis in Micropterus salmoides: Implications for Inflammatory Regulation and Liver Health - Quanquan Cao; Ju Zhao; Xuefei Zhang; Laia Ribas; Haifeng Liu; Jun Jiang (Biology)
Fish meal (FM) is a crucial high-quality protein source in aquafeeds, prized for its excellent palatability, high digestibility, and rich protein content [...]